Facile approach for omniphobic and anti-icing on Fe surface - Nguyen, Thanh-Binh; Boudkhamchampa, Khamla; Bui, Thi Trang; Dang, Minh Hung (Communications in Physics, 2023)
The functionalized process refers to a new concept, which aims to modify the physical and chemical properties of the original surface for specific purposes. Hence, the functional surfaces will introduce the desired properties that can not be found in the original material. The various applications might be named liquid repellent, anti-icing, anti-reflection, water harvesting, anti-biofouling, etc. This study proposes a simple and fast fabrication method based on etching incorporated with low surface energy chemical compound coating to functionalize the Iron (Fe) surface for omniphobic and anti-icing characteristics. After being functionalized, the surface reveals an omniphobic state with various liquids and extremely low adhesion to ice bulk. The research might suggest solutions for manufacturing functional surfaces oriented to outdoor applications such as windshields, rearview mirrors, anti-fouling surfaces, etc